Values depicted in selected science textbooks used by grades five and six pupils: An analysis - Gundaya, Rosenda P. (Animo Repository, 1998)
This study is an analysis of values reflected in the Grades V and VI science textbooks and the congruence of these values with the Grades V and VI Science Minimum Learning Competencies (MLC).To attain the above objectives, the descriptive method of research particularly the content analysis as a way of identifying the values reflected in the science textbooks was used.The main sources of the data were the most commonly used textbooks in science for Grades V and VI in the province of Nueva Vizcaya. Eight science textbooks were analyzed: four for Grade V and four for Grade VI.Based on the data gathered, the following were noted:All values found in the DECS Values Education Framework which are designated as core and related values were the specific values reflected in the Grades V and VI science textbooks.The values that were dominantly reflected in the Grades V and VI science textbooks were ranked in the following order: Grade V science textbooks: first, knowledge/truth second, health/harmony with nature third, spirituality fourth, social responsibility fifth, love then closely followed by economic efficiency which is sixth in rank then finally nationalism/global solidarity as the seventh. In Grade VI science textbooks, knowledge/truth outranked the other core values, followed by health/harmony with nature, second love, third very closely followed by economic efficiency, fourth fifth, social responsibility and also very closely followed by spirituality, sixth and seventh is nationalism/global solidarity. The STAR One-Way Analysis of Variance was used to determine the significant difference of the values reflected in the Grades V and VI science textbooks. Among the seven core values as Health/Harmony with Nature, Knowledge/Truth, Love, Spirituality, Social Responsibility, Economic Efficiency, and Nationalism/Global Solidarity, only one core value, Economic Efficiency, was revealed to be significantly different at .05 level in the values reflected in Grades V and VI science textbooks. In the other six core values, there was no significant difference in the values reflected in Grades V and VI science textbooks.The analyzed Grades V and VI science textbooks are congruent with the Grades V and VI Science Minimum Learning Competencies with respect to the values contained in the general topics.